تكامل نماذج الشبكات العصبيّة الاصطناعيّة والخوارزميّات الجينيّة في استكمال بيانات الهطل المطري - عمار, غطفان; سليمان, علاء; الدرويش, عامر (Latakia University Journal -Engineering Sciences Series, 2019)
Accurate and reliable modeling of precipitation data is an important step in managing water and rivers, especially under the influence global climate change. This requires long time series of hydrological data, but these sequences often contain missing values.This research includes the using of artificial neural networks (ANNs) models with feed forward and back propagation of error with genetic algorithms (GAs) in the process of filling gaps in daily precipitation data, where genetic algorithms were used to determine the optimal structure of the artificial neural network, after that artificial neural networks were trained using the back propagation algorithm, in order to obtain the best performance of the artificial neural network models (ANNs) in predicting the lost values ​​of daily precipitation, thus obtaining complete time series of daily precipitation in the study area. The values of root mean square errors and correlation coefficients were used to evaluate the performance of the models and compare them according to the different input and output values of the meteostations (Satha -Ain Al-Krum-Al-Kareem-Al-Sakilibia) during the period (1994-2002), simulating the various possible losses of data from the meteostation. This study recommends the application of hybrid systems of artificial intelligence models to improve the efficiency of predicting models of weather factors and other water resources factors in different regions of Syria. لا شك أن نمذجة الأمطار بدقة وموثوقية هي خطوة هامة في إدارة المياه والأنهار، ومواجهة تغيرات المناخ العالمية، وهذا يتطلب سلاسل طويلة من البيانات الهيدرولوجية، غير أن هذه السلاسل في كثير من الأحيان تحوي على قيم مفقودة. يتضمن هذا البحث استخدام نماذج الشبكات العصبية الاصطناعية ذات التغذية الأمامية والانتشار العكسي للخطأ مع الخوارزميات الجينية (GAs) في عملية ملء الثغرات في بيانات الأمطار اليومية في منطقة سهل الغاب، حيث استخدمت الخوارزميات الجينية في تحديد الهيكلية المثلى للشبكة العصبية الاصطناعية، ثم دربت مجموعة من الشبكات العصبية الاصطناعية وفق الهيكلية الناتجة باستخدام خوارزمية الانتشار العكسي للخطأ ، وذلك بهدف الحصول على أفضل أداء لنماذج الشبكات العصبية الاصطناعية (ANNs) في التنبؤ بالقيم المفقودة للأمطار اليومية، وبالتالي الحصول على سلاسل كاملة للهطل المطري اليومي في منطقة الدراسة. لقد استُخدمت قيم جذر متوسط مربعات الأخطاء ، ومعامل الارتباط لتقييم أداء النماذج والمقارنة فيما بينها وفق مختلف قيم المدخلات والمخرجات للمحطات المطرية (شطحة – عين الكروم – الكريم – السقيلبية) خلال الفترة (2002-1994)، بحيث تحاكي مختلف حالات الفقد الممكنة للبيانات من المحطة الهدف أو المحطات المجاورة، وتوصلت هذه الدراسة إلى نتائج جيدة لجميع النماذج، وتوصي الدراسة بتطبيق الأنظمة الهجينة من نماذج الذكاء الاصطناعي لتحسين كفاءة نماذج التنبؤ بالعناصر المناخية وغيرها من العوامل المتعلقة بالموارد المائية في مناطق مختلفة من سورية.